Model Pengasuhan Santri di Pesantren: Integrasi Tarbiyah Islam dan Tantangan Modern - Permatasari, Indah Gilang; Rasyid, Faiz; Alfajri, Hamzah; Taufiqurrahman, Taufiqurrahman (TSAQOFAH, 2026)
Research on the care and upbringing of santri in pesantren has been widely conducted, yet studies that systematically integrate the conceptual aspects of tarbiyah Islam, caregiving patterns, the role of musyrif, and caregiving challenges in the digital era remain limited. This study aims to analyze the concept and implementation of santri care in pesantren and to identify factors that influence the effectiveness of santri character development amid modern social dynamics. It employs a qualitative approach with a literature study design through the analysis of scholarly literature, pesantren documents, and previous research. The data were examined using thematic analysis to identify the main patterns of caregiving. The findings indicate that santri care in pesantren is a holistic guidance process encompassing spiritual, moral, and social dimensions, in which the role of the musyrif is highly strategic as mentor, supervisor, and role model for santri. Emerging challenges, including the penetration of digital technology, the heterogeneity of santri characteristics, and limited caregiver competencies, necessitate the adaptation of caregiving models that are more professional, humanistic, and contextually responsive. This study contributes to strengthening tarbiyah Islam theory and character education in the pesantren context, while providing practical implications for the development of caregiving policies that are responsive to contemporary change.